Evaluation of synthetic wheat lines (Triticum durum/Aegilops tausсhii) for vegetative period and resistance to diseases - V. P. Shamanin; I. V. Pototskaya; S. S. Shepelev; V. E. Pozherukova; A. Yu. Truschenko; A. S. Chursin; A. I. Morgunov (Вавиловский журнал генетики и селекции, 2017)
The growth of the total wheat production and increase of yield stability from year to year are some of the priorities of agriculture in Russia. The yield of commercial varieties significantly diversifies due to huge losses of their potential under the influence of negative biotic and abiotic factors. Increase of resistance to stress factors in the emerging varieties can be achieved by utilizing the diversity of the genetic resources of related wild species and genera in crosses. The results of a phenotypic evaluation of the synthetic hexaploid wheat lines of CIMMYT breeding created by crossing durum wheat varieties from Institute of Breeding and Genetics (Odessa, Ukraine) and variety Pandur from Romania (T. durum Desf., AB genome) with Aegilops (Ae. tausshii Coss., D genome), and also 15 synthetic wheat lines of Kyoto University breeding (Japan) created by crossing durum wheat variety Langdon with different ecological forms Aegilops are presented. Research was performed on the experimental field of Omsk SAU under conditions of southern forest-steppe of West Siberia in 2016. Between synthetics, there was revealed a genotypic difference in the vegetative period duration and resistance to diseases. Lines of hybrid combination Aisberg/Ae.sq.(511) were characterized as the most early-maturity genotypes among the lines studied. The hybrid combinations Ae.sq.(369) with variety Aisberg, Ae.sq.(310) and Ukr-Od 1530, Ae.sq.(223) and Pandur are characterized by complex resistance to fungal diseases. Most of the lines demonstrated high and moderate resistance to rust fungus, severity ranging from 5 to 70 % and severity of powdery mildew being 10–90 %. Lines derived from variety Ukr-Od 1530.94 and accessions Ae. tauschii (392); (629); (1027); (1031) and lines Langdon/Ku-2074; Langdon/Ku-2075; Langdon/Ku-2100; Langdon/Ku-2079 are characterized by complex resistance to powdery mildew, leaf and stem rust. The synthetic lines with a complex of economically valuable traits present interest as an initial material for breeding programs.